Comparison of the Empirical Performance of Minisat and GSAT Solvers on SATLIB Benchmark - A.J. Kawu; G. M. Wajiga; Y. M. Malgwi, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
In this study, the effectiveness of Minisat(Minimal SAT solver) and Greedy Randomized Adaptive Search (GSAT, Simulated Annealing option) solvers is compared on a number of SATLIB Benchmark problems. Gaining understanding of their effectiveness in resolving SAT cases was the main objective, with an emphasis on application and randomly generated instances. The experimentation showed that Minisat performed better than GSAT in every case, proving to have better solution abilities. A 2.40GHz Core i5 CPU, fitted in a Dell Latitude E7470 laptop, was used for the experiments. All things considered, this research helps to compare the strengths and weaknesses of the GSAT and Minisat solvers and provides insightful information about SAT problem-solving techniques.